Synthesis and characterizations of phosphorene added graphene prepared via solid state reactions - Soong, Meng Keong (2022)
Graphene-based hybrid materials have been extensively used in widely range application such as electronic mobility, energy storage, electrochemical application and sensing device. Many of energy storage system of devices involved of graphene reinforce metal or polymer matrix composites for enhance electrical conductivity, energy storage performance and the energy capacity storage. Graphene been chosen as potential material due to its unusual electrical and mechanical properties such as large surface is for better movement of electrical charge and discharge, tensile strength are high and excellent electric conductive materials. The phosphorene used to overcome graphene theoretical value of the low energy capacity due to the graphene powder aggregation. Phosphorene, exfoliation of single layer black phosphorus possessed similar atoms with graphene where its stable in electrical conductivity and is most stable allotrope of the phosphorene with van der-Waals heterostructures are compatibles with graphene to perform a strong bonding of structure. In this research, solid state reaction is used for stability of both materials, graphene and phosphorene hybrid as well as to avoid the restacking graphene layer to cause large surface energy affected the ions storage capacity. Apart from that the method advantage low energy consumption and avoid chemical reaction process. The research will prepare phosphorene/graphene concentration ratio that is 02:1, 0.4:1, 0.6:1, 0.8:1, and 1:1 in solid state reaction method. The samples will be characterized of it structural properties by using XRD, FTIR and SEM while the investigation on energy storage performance include its electrical conductivity will be conducted by using four-point probe equipment correlation with correction factor formula.